2013
DOI: 10.1159/000350228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bronchodilators on Regional Lung Sound Distribution in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Bronchodilators have been reported to influence regional lung ventilation in patients with chronic obstructive pulmonary disease (COPD), which may change regional lung sound distribution. Vibration response imaging (VRI) is a lung imaging system for the assessment of breath sounds. Objective: To evaluate the effects of a short-acting β2-agonist (SABA) on the regional distribution of lung sounds in COPD patients. Methods: A double-blind crossover trial was performed to compare the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Since we did not find significant correlations between either AS or age in the control group, we believe that the difference in age between healthy subjects and COPD patients did not influence the higher AS in COPD patients. Furthermore, we did not define a washout time for 19 patients with bronchodilator treatment, although bronchodilator use for COPD patients was reported to change the distribution of the lung sounds [12]. However, we revealed positive correlations between AS and heterogeneity of emphysema distribution in 22 patients with no bronchodilator treatments.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Since we did not find significant correlations between either AS or age in the control group, we believe that the difference in age between healthy subjects and COPD patients did not influence the higher AS in COPD patients. Furthermore, we did not define a washout time for 19 patients with bronchodilator treatment, although bronchodilator use for COPD patients was reported to change the distribution of the lung sounds [12]. However, we revealed positive correlations between AS and heterogeneity of emphysema distribution in 22 patients with no bronchodilator treatments.…”
Section: Discussionmentioning
confidence: 75%
“…Although there are many investigations regarding lung sound amplitude, transmission, distribution, or adventitious sounds [3,4,5,6,7,10,12,14,20,21], there are only a few reports to study lung sound asynchrony [8,9,13,15]. Wang et al [9] revealed that asynchrony between the left and right lung in asthma exacerbations was significantly reduced after clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations